2015
DOI: 10.6061/clinics/2015(02)10
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ischemic preconditioning in a pig model of large-for-size liver transplantation

Abstract: OBJECTIVE:In most cases of pediatric liver transplantation, the clinical scenario of large-for-size transplants can lead to hepatic dysfunction and a decreased blood supply to the liver graft. The objective of the present experimental investigation was to evaluate the effects of ischemic preconditioning on this clinical entity.METHODS:Eighteen pigs were divided into three groups and underwent liver transplantation: a control group, in which the weights of the donors were similar to those of the recipients, a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 40 publications
2
18
0
Order By: Relevance
“…Corroborating our findings, other studies using RIPC, but in different experimental models, also identified an elevation of IL-6 serum levels and IL-6 mRNA 15,16 .…”
Section: Discussionsupporting
confidence: 89%
“…Corroborating our findings, other studies using RIPC, but in different experimental models, also identified an elevation of IL-6 serum levels and IL-6 mRNA 15,16 .…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, the e‐NOS gene was more highly expressed in the liver parenchyma of the LFS than the LFS+SHUNT group recipients. This gene is thought to be responsible for the production of nitric oxide, which is beneficial because it can lead to vasodilatation and the softening of ischemia–reperfusion lesion . Finally, these molecular findings may suggest an exacerbation of IRI promoted by the shunt, as gene expression is an immediate response and is a reflection of the low portal and arterial flow presented by SHUNT recipients one hour after reperfusion.…”
Section: Discussionmentioning
confidence: 99%
“…This situation can lead to reduced blood supply to the liver graft with higher incidences of graft dysfunction, acute rejection, and vascular complications. 1 IRI is one of the main mechanisms of graft injury in liver transplantation, [4][5][6] leading to complications such as poor graft function. 7 C-Fos and c-Jun are IEG that are activated precociously after IRI and regulate tissue responses to injury stimulation.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier study on IPC has reported anti‐inflammatory action in liver transplants by inducing the expression level of peroxisomal proliferator‐activated receptor–α (PPAR–α) and adiponectin which inhibit NFκB inflammatory cascade . In addition, a suppressive effect on TNF–α expression and serum levels of interleukin‐6 (IL‐6) have been reported for the positive effects in liver graft survival …”
Section: Introductionmentioning
confidence: 99%